The Efficient Techniques for Non-Linear Fractional View Analysis of the KdV Equation - Khan, Hassan; Khan, Qasim; Tchier, Fairouz; Singh, Gurpreet; Kumam, Poom; Ullah, Ibrar; Sitthithakerngkiet, Kanokwan; Tawfiq, Ferdous (Frontiers in Physics, 2022)
The solutions to fractional differentials equations are very difficult to investigate. In particular, the solutions of fractional partial differential equations are challenging tasks for mathematicians. In the present article, an extension to this idea is presented to obtain the solutions of non-linear fractional Korteweg–de Vries equations. The solutions comparison of the proposed problems is done via two analytical procedures, which are known as the Residual power series method (RPSM) and q-HATM, respectively. The graphical and tabular analysis are presented to show the reliability and competency of the suggested techniques. The comparison has shown the greater contact between exact, RPSM, and q-HATM solutions. The fractional solutions are in good control and provide many important dynamics of the given problems.